2003
DOI: 10.1152/ajpendo.00150.2003
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal lysine metabolism is driven by the enteral availability of dietary lysine in piglets fed a bolus meal

Abstract: Intestinal lysine metabolism is driven by the enteral availability of dietary lysine in piglets fed a bolus meal. Am J Physiol Endocrinol Metab 285: E1246-E1257, 2003. First published August 8, 2003 10.1152/ajpendo.00150.2003.-Previous steady-state continuous-feeding studies have shown that the gut mucosa removes substantial amounts of both dietary and systemic amino acids. However, enteral nutrition is often given under non-steady-state conditions as a bolus meal, and this has been shown to influence systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
(80 reference statements)
1
28
0
Order By: Relevance
“…These results indicated that, despite the difference in methionine First-pass use of methionine by the intestinesources, the first-pass utilisation of dietary methionine by the intestine remained at about 30 % of intake. Similar results in piglets fed milk protein have been obtained in a previous study (7) , in which dietary methionine intake is about 1·5-fold that in the present study. These results suggested that the fraction of methionine may be more constant than the absolute amount of methionine that is extracted by the intestine in its first-pass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that, despite the difference in methionine First-pass use of methionine by the intestinesources, the first-pass utilisation of dietary methionine by the intestine remained at about 30 % of intake. Similar results in piglets fed milk protein have been obtained in a previous study (7) , in which dietary methionine intake is about 1·5-fold that in the present study. These results suggested that the fraction of methionine may be more constant than the absolute amount of methionine that is extracted by the intestine in its first-pass.…”
Section: Discussionsupporting
confidence: 92%
“…From 08.00 to 14.00 hours, pigs were offered meals at hourly intervals, and the meal was the equivalent of one twenty-fourth of the daily intake (45 g/kg BW). Immediately after the first meal, piglets received a constant infusion of [1-13 C]methionine, suspended in water via the gastric catheter at a rate of about 0·25 ml/min to provide [1][2][3][4][5][6][7][8][9][10][11][12][13] C]methionine at 7·0 mmol/kg BW per h. After the tracer infusion was started, the piglets continued to receive hourly meals. Arterial and portal blood samples were taken at hourly intervals until 6 h of tracer infusion, and all the blood samples were immediately placed on ice.…”
Section: Infusion Protocol and Blood Collectionmentioning
confidence: 99%
“…The primed, continuous infusion rate was 10 mol⅐kg Ϫ1 ⅐h Ϫ1 for each methionine tracer, so the total isotopic methionine infusion rate was 20 mol⅐kg Ϫ1 ⅐h Ϫ1 . Arterial and portal blood samples were collected at 0, 90, 115, and 120 min and 6, 7, and 8 h. Portal blood f low was monitored continuously by transit-time ultrasound for 30 min before the initial formula feeding and throughout the entire 8-h protocol as described (24,26). After tracer infusion on the second study day, animals were euthanized (Beutanasia-D; Schering-Plough Animal Health, Kenilworth, NJ) and intestinal, pancreas, stomach, and liver tissues were collected and frozen at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Other tissues with higher intracellular homocysteine enrichments than in the plasma, including the small intestine, may also contribute to the homocysteinaemia (55) . As regards cysteine in the GIT, studies in pigs indicate that less than 100 % of dietary cysteine appears in the portal blood, suggesting intestinal utilisation of cysteine (47,58) . The first step in cysteine catabolism is its conversion to cysteine sulfinate via the enzyme cysteine dioxygenase (CDO) (Fig.…”
Section: Evidence Of Intestinal Sulfur Amino Acid Metabolismmentioning
confidence: 99%